Key Considerations on the Authority of the Commercial Court and the State Court in Debt Qualification - Marpaung, Abdul Hakim; Sunarmi, Sunarmi; Robert, Robert (Jurnal Hukum Replik, 2024)
Article 1, Clause 6 of Law Number 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations defines debt, but confusion often arises when cases that should fall under the District Court's authority are instead handled by the Commercial Court, especially regarding debt proof. This thesis examines the evolution of debt in Indonesian bankruptcy law, the application of simple debt proof, and the overlap of jurisdiction between District and Commercial Courts in bankruptcy cases. The research, based on a normative legal approach using statutory, case-based, and historical methods, identifies that the concept of debt in Indonesia has evolved significantly, starting from Failisement Verordening to Law No. 37/2004, reflecting the need for refined legal mechanisms. Simple proof of debt is established when the debtor has two or more creditors and fails to pay at least one due and collectible debt, with creditors required to meet specific conditions to prove default. Jurisdiction between the Commercial and District Courts depends on the complexity of evidence—straightforward cases go to the Commercial Court, while complex ones fall under the District Court’s authority. However, the ambiguity in defining the respective authority of each court persists, highlighting the need for amending Article 1, Clause 6 of Law No. 37/2004 to establish clearer benchmarks for simple evidentiary standards in debt-related cases.Keywords: Bankruptcy, Debt, Commercial Court, District Court, Legal Authority, Indonesia.